(untitled) (Research, Society and Development, 2023)
Objective: This study aims to identify the reasons associated with the interruption of Exclusive Breastfeeding among nursing mothers during the first six months of the baby’s life. Method: This is a descriptive, exploratory, cross-sectional study with a quantitative approach, whose search will be from August to September 2022. The research involves investigating the practice of exclusive breastfeeding through a questionnaire prepared by the researchers , and correlating its results with a bibliographic survey on the subject. Results and Discussion: Based on the data collection, it was found that Exclusive Breastfeeding is still a little widespread practice among puerperal women in the city of Imperatriz-MA, despite having a valuable importance in the child’s health, reflecting the need to interventions that disseminate this practice and prevent the problems caused by early weaning. Conclusion: The research showed that there is a need to intensify public policies aimed at the main factors inherent to early weaning, as well as the implementation of interventions through actions, especially within Primary Care, provided by qualified professionals that enable the renewal knowledge, helping to develop strategies that bring benefits in terms of newborn nutrition and care for women.